Internalisasi Ecological Citizenship: Sebuah Tinjauan Komparatif Pendidikan Kewarganegaraan di Universitas Jambi dan Universitas Muhammadiyah Tasikmalaya - Melisa; Ichsan, Muhammad; Nugraha, Fajar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze and compare the integration of ecological citizenship values within the Civic Education curriculum at Universitas Jambi and Universitas Muhammadiyah Tasikmalaya. Method: The study employs a qualitative case study approach with a comparative design. Subjects: The participants included lecturers and students from the Civic Education departments in both universities. Instruments: Data were gathered through semi-structured interviews, classroom observations, and document analysis of semester lesson plans. Data collection: Techniques involved thematic observation and in-depth interviews. Data analysis: Data were analyzed using systemic condensation, involving data display and conclusion drawing. Findings: The results indicate that Universitas Jambi focuses on ecological responsibility related to regional forest preservation, while Universitas Muhammadiyah Tasikmalaya emphasizes urban environmental ethics and religious-based conservation. Both institutions face challenges in transforming theoretical knowledge into consistent ecological advocacy among students.